IMPLEMENTATION OF TECHNOLOGY IN LEARNING - Elmiwati Elmiwati; Agus Fawait; Ismaul Fitroh; Antono Damayanto; Agus Rofi'i (International Journal of Teaching and Learning, 2024)
Technological developments that continue from time to time provide media products that can be used in educational aspects. Whatever type of technology and media is used, the most important thing that must be prioritized is how the two-way interaction between students and their educators must be reciprocal with each other. The choice of type of technology used will usually be adjusted to the needs of education and training providers. Because, there is no technology that is best than each other, but technology that can adapt and be fun, so that it can achieve effective learning goals. The purpose of this study is to provide an overview of how technology is used in education. Research in which the research object is examined using a variety of library resources is known as library data collecting. This research is characterized by descriptive analysis, which entails routinely analyzing the collected data and then offering clarification and insight to ensure the reader understands it fully. The internet is used by the data gathering approach to look up different book references and earlier research publications that are relevant to the study discussion issue. The conclusion of this research is that technology facilitates the development of critical skills, creativity and problem solving needed to face the demands of an increasingly digital world of work. One of the roles of technology in teaching is to facilitate teacher and student access to various teaching and educational resources.